La gestión documental en la dirección de agua potable y alcantarillado [DAPAL] del cantón Latacunga en el período 2022-2023. - Cando Arequipa, Lisbeth Jeaneth (2023)
Document Management is the set of specialized rules and practices used to prepare and supervise documents of various kinds, both obtained and produced, which are part of the assets of public institutions and private companies. For this reason, the purpose of this research is to provide Document Management strategies to improve the management of information in the DAPAL Direction, because there are deficiencies in the management of documentation which has generated loss and destruction of this institutional treasure. The research has a quantitative approach of descriptive level, bibliographic and field research was also applied. In addition, the survey technique was used for data collection, which was validated by means of expert judgments, and the questionnaire was elaborated using a Likert scale with 28 items, allowing the collection of information to support the work and seek improvement strategies in the areas in which there are weaknesses when it comes to proper document management. Thus, 68% of the findings show that very few protocols and manuals are handled for the reception, expurgation, foliation and security of the files, in addition to the disposition of the documents, which undoubtedly puts the information at risk and generates mistrust. Consequently, the alternative solutions are focused on the National Technical Rule, in order to solve the difficulties encountered, it was proposed to generate document management strategies aimed at guaranteeing adequate document management.